Parenting support in ECEC services: the views of practitioners implementing a model in the Irish context about parents’ engagement and associated outcomes - Catarina Leitão; Jefrey Shumba (Frontiers in Sociology)
IntroductionProviding parenting support in combination with Early Childhood Education and Care (ECEC) can positively impact children’s and families’ wellbeing. This study aimed to explore factors potentially affecting parents’ engagement in a parenting support model in ECEC services and associated outcomes. This model involves a professional role dedicated to working with parents, the Parent Carer Facilitator (PCF).MethodsEight PCFs and seven managers of ECEC services in Ireland implementing this model were interviewed. Data were analysed through thematic analysis.ResultsFour themes were generated: factors related to parents’ engagement, approaches to promoting engagement and responsiveness to families’ needs, implementation drivers and relevance of the model.DiscussionFindings indicated that a professional role dedicated to supporting parents within ECEC services, focusing on establishing trusting relationships and tailoring support according to families’ needs, can foster parents’ engagement in the support offered and positive outcomes regarding parenting and parents-ECEC service relationship.